Fattening heifers for the summer or early fall market - Pickett, A.G.; Smith, E.F. (Kansas Agricultural Experiment Station, 2012)
The previous tests with heifer calves have been completed. Pasture was not used in these tests but instead, heifer calves were fed a full feed of grain, three-fourths feed, one-half feed, one-fourth feed and no grain, respectively with silage and a protein supplement. As a result of these tests it was determined that for heifer calves which are to be full fed grain in the dry lot or which are to be grazed 75 to 100 days and then full fed grain for approximately 100 days, two to two and one-half pounds of grain in the winter ration will produce enough flesh to result in U. S. Good carcasses after 100 days of full feeding, yet not too much flesh to justify grazing 75-100 days before full feeding. Beginning with this, the fourth test, a study was initiated to determine the best way to utilize bluestem and brome grass in fattening heifers.
Keywords: Beef; Heifers; Market; Bluestem pasture